2022
DOI: 10.2147/dmso.s342505
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between GGT/HDL and MAFLD: A Cross-Sectional Study

Abstract: To explore the association between γ-glutamyl transpeptidase to high-density lipoprotein ratio (GGT/HDL), triglyceride glucose-body mass index (TYG-BMI), and metabolic associated fatty liver disease (MAFLD) in a Chinese population with type 2 diabetes (T2DM) by cross-sectional analysis. To investigate the role of GGT/HDL played in MAFLD by TYG-BMI. Patients and Methods: A total of 1434 adult patients hospitalized with T2DM at Hebei General Hospital (Shijiazhuang, China) were included in the study. Patients' de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 60 publications
(57 reference statements)
0
21
2
1
Order By: Relevance
“…A more convenient and cheaper IR measurement is critical for prospective risk assessment, extensive population screening, and treatment monitoring. Triglyceride glucose-body mass index (TyG-BMI) is a new obesity-related parameter that has been developed in recent years, and it's obtained by multiplying TyG (composed of fasting plasma glucose and triglycerides) with BMI (derived from weight and height) (13)(14)(15)(16)(17)(18)(19)(20)(21). These are routine physical examination indicators that are easy to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…A more convenient and cheaper IR measurement is critical for prospective risk assessment, extensive population screening, and treatment monitoring. Triglyceride glucose-body mass index (TyG-BMI) is a new obesity-related parameter that has been developed in recent years, and it's obtained by multiplying TyG (composed of fasting plasma glucose and triglycerides) with BMI (derived from weight and height) (13)(14)(15)(16)(17)(18)(19)(20)(21). These are routine physical examination indicators that are easy to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the function of the ratio was the combination of the two indicators and might exert a predictive value on the prevalence of NAFLD or other related metabolic disorders [7]. A recent cross-section study in a Chinese population of T2DM patients also found that in the overweight (BMI greater than 23 kg/m 2 ) subgroup, the GGT/HDL-C has a positive relationship with NAFLD incidence [35]. Our study is the rst to highlight the role of the GGT/HDL-C ratio in T2DM and further con rm a non-linear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that GGT 15 , HDL 16 , and NAFLD 17 , 18 are all associated with insulin resistance. Also, recent studies have found that increased levels of the GGT/HDL‐c ratio were strongly related to the risk of NAFLD and MAFLD 12 , 13 . Therefore, we propose that the GGT/HDL‐c ratio may affect the development of diabetes by mediating insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have found that high‐density lipoprotein cholesterol (HDL‐c) and γ‐glutamyl transpeptidase (GGT) were related to non‐alcoholic fatty liver disease (NAFLD) 5 , 6 , 7 , 8 and type 2 diabetes mellitus 9 , 10 , 11 risk. Two recent cross‐sectional studies have demonstrated that increased levels of the GGT/HDL‐c ratio were strongly associated with NAFLD and metabolic‐associated fatty liver disease (MAFLD) 12 , 13 . However, when reviewing the literature, we noticed no evidence of the connection between GGT/HDL‐c and the risk of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%